THE INFLUENCE OF SOCIALIZATION, KNOWLEDGE AND RELIGIUS ON EMPLOYEE PERFORMANCE - Hasibuan, Lempang; Supriyanto, Achmad Sani; Ekowati, Vivin Maharani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to determine the influence of socialization, knowledge, and religiosity on the performance of Bank Syariah Indonesia (BSI) Malang City employees. The population of this study consisted of employees and customers of Bank Syariah Indonesia (BSI) Malang City, totaling 200 respondents. The sample in this study was 200, and the respondents in the questionnaires returned were 112. This type of quantitative research uses a sample determination technique using probability sampling techniques . The data source in this research is primary data. The data collection method was carried out using a Google Document questionnaire. Meanwhile, the data was analyzed using Partial Least Square (PLS). The dependent variables of this research are employee performance and trust. The independent variables include socialization, knowledge, and religiosity.